Protective effect of different parts of Cassia fistula on human umbilical vein endothelial cells against glycated protein-induced toxicity in vitro - Einstein, J.W.; Mustafa, Mohd Rais; Nishigaki, I.; Rajkapoor, B.; Mohd, M.A. (Prous Science, 2008)
The protective effect of methanol extracts of Cassia fistula (flowers, leaves and bark) was examined in vitro in human umbilical vein endothelial cells (HUVEC) against toxicity induced by glycated protein (GFBS) in vitro. The experiments consisted of eight groups of HUVEC with five flasks in each group. Group I was treated with 15 FBS, group II with GFBS (70 microM) alone, and the other six groups were treated with GFBS plus 25 and 50 microg of each of the three types of C. fistula extracts. After 72 h of incubation, cells were collected and tested for lipid peroxidation, antioxidant enzyme activities and glutathione S-transferase (GST). The protective effect of C. fistula extracts against GFBS-induced cytotoxicity was examined in HUVEC by using trypan blue exclusion and MTT assays. Results showed that HUVEC incubated with GFBS alone showed a significant (P < 0.001) elevation of lipid peroxidation accompanied by depletion of superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx) and glutathione reductase (GR), in addition to decreased cytosolic GST. Treatment of HUVEC with C. fistula extracts at a concentration of 25 and 50 microg significantly decreased lipid peroxidation and normalized the activities of the antioxidant enzymes and GST levels in a concentration-dependent manner. Morphological changes of HUVEC were compared with respective controls; in addition, the C. fistula extracts increased the viability of HUVEC damaged by GFBS. A protective effect of C. fistula extracts on HUVEC against GFBS-induced toxicity suggested a potential beneficial effect of the extract in preventing diabetic angiopathies.